2018
DOI: 10.2135/cropsci2018.02.0115
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Spectral Reflectance of Maize Seedlings and Its Relationship to Cold Tolerance

Abstract: Increasing early‐season cold tolerance of maize (Zea mays L.) has the potential to lengthen its growing season, reduce its environmental impact, and enhance its yields. Cold‐ and warm‐grown plants differ for biomass accumulation and spectral reflectance, the latter caused by differences in leaf chlorophyll content, carotenoid content, or other chemical and morphological attributes. Here, we evaluate genetic leaf spectral reflectance diversity across 38 inbred and 14 hybrid maize genotypes grown in cold and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 47 publications
3
15
0
2
Order By: Relevance
“…However, identifying more subtle symptoms such as those caused by abiotic stresses can be challenging. Pandey et al (2017) found hyperspectral imaging to be useful in quantifying plant leaf chemical properties that could aid in detecting water and nutrient deficiencies among crops and Obeidat et al (2018) discovered that spectral indices correlated with chlorophyll content could help distinguish between genotypes and cold-stressed plants in indoor settings. Similarly, Behmann et al (2014) found that hyperspectral imaging can be used to cluster barley plant pixels into different levels of drought-stress based on amount of chlorosis and senescence.…”
Section: Core Ideasmentioning
confidence: 99%
See 2 more Smart Citations
“…However, identifying more subtle symptoms such as those caused by abiotic stresses can be challenging. Pandey et al (2017) found hyperspectral imaging to be useful in quantifying plant leaf chemical properties that could aid in detecting water and nutrient deficiencies among crops and Obeidat et al (2018) discovered that spectral indices correlated with chlorophyll content could help distinguish between genotypes and cold-stressed plants in indoor settings. Similarly, Behmann et al (2014) found that hyperspectral imaging can be used to cluster barley plant pixels into different levels of drought-stress based on amount of chlorosis and senescence.…”
Section: Core Ideasmentioning
confidence: 99%
“…Fewer studies have used hyperspectral profiling to separate different genotypes or lines of the same species. A study by Obeidat et al (2018) showed that genotype main effects across short-season maize lines significantly contributed to variation in various spectral reflectance indices and spectral reflectance in the visible and near-infrared range when comparing hyperspectral scans of flat leaves. This variation, particularly in the spectral reflectance across the visible range of the spectrum, was likely due to chlorophyll and carotenoid differences (Obeidat et al, 2018).…”
Section: Ability To Distinguish Genotypes Using Hyperspectral Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with IRT, plant phenotyping spectral reflectance indices related to plant photosynthetic status such as leaf and crown chlorophyll concentration [57][58][59][60], obtained in situ and noninvasively, can reflect the health state of plants. After all, chlorophyll as a pivotal photosynthetic pigment on which plant growth and productivity depend [60,61], is considered a hallmark index to plant health estimation [62][63][64].…”
Section: Introductionmentioning
confidence: 99%
“…A 206 study by Obeidat et al (2018) showed that genotype main effects across short-season maize lines 207 significantly contributed to variation in various spectral reflectance indices as well as spectral 208 reflectance in the visible and near-infrared range when comparing hyperspectral scans of flat 209leaves. This variation, particularly in the spectral reflectance across the visible range of the 210 spectrum, was likely due to chlorophyll and carotenoid differences(Obeidat et al, 2018). To 211 assess variation in spectral reflectance among maize genotypes, we applied our leaf segmentation 212 approach to compare the reflectance values across individual leaf segments among the different 213 inbred lines grown in control conditions in experiment E1.…”
mentioning
confidence: 99%